Pemanfaatan Teknologi Informasi dan Komunikasi dalam Layanan Bimbingan dan Konseling di Sekolah : Problematika dan Solusinya - Ilfana, Aulia; Herdi, Herdi (Jurnal Paedagogy, 2022)
This study aims to describe the benefits of information technology in Guidance and Counseling services in schools. This research method uses a literature study which contains the concepts and theories used based on the available literature, especially from articles published in various scientific journals. Furthermore, the data analysis technique used interpretive descriptive analysis. The results of this study indicate that information and communication technology is an important factor in the process of guidance and counseling services by BK teachers or school counselors. The use of information and communication technology is expected to encourage BK teachers or counselors to be more creative, innovative, varied in seeking the latest information in the service process. Technology must be used as well and optimally as possible by the guidance and counseling teacher or counselor so that the services provided can provide optimal results.